Investigation of saw wood dust with different percentages in sand brick ratio 1:3 - Zuriyani, Zulkifli (2015)
Concern of environmental issues especially related to the river pollution and air pollution has attracting effort to produce sustainable construction material made of by product from industrial waste such as wood dust. The increasing price of the construction materials also become of the factor for researcher to find an alternative for construction materials replacement. The purpose of this research is to study the saw wood dust on the sand brick strength and engineering properties. The experiment have been conducted using saw wood dust as replacement material for sand in proportion 5%, 10%, 15% and 20%. Control samples contain 0% of wood dust is use to compare the data obtained with the samples containing wood dust. The water cement ratio was determined by using trial and error with cement to sand ratio 1:3. The mixes are cured using two types which is air and water curing for 7 and 30 days. Then the number of samples were tested for compressive strength, water absorption and dimension test. Based on the result of the experiments, it shows that the objectives were achieved. The strength of the saw wood dust bricks decrease with the increasing of saw wood dust percentages. The saw wood dust bricks did not suitable to be used as a load bearing wall in the construction due to the lower compressive strength and higher water absorption rates.